Penguatan Karakter melalui Penggalian Kearifan Lokal Kediri bagi Karang Taruna Desa Rejomulyo Kecamatan Pesantren Kota Kediri - Laila, Alfi; Mukmin, Bagus Amirul; Permana, Erwin Putera; Imron, Ilmawati Fahmi; Saidah, Karimatus; Putri, Kharisma Eka; Primasatya, Nurita; Damariswara, Rian; Wiguna, Frans Aditia; Angzalna, Umbar (Universitas Nusantara PGRI Kediri, 2024)
The influence of the rapid development of technology has begun to shift the character of society, including the people in Rejomulyo Village, Islamic Boarding School District, Kediri City. As an urban society, we cannot be separated from the use of technology which is categorized as high. To prevent the negative impact of the use of technology, it is necessary to strengthen character values ​​in the Rejomulyo Village community, especially village youth or known as youth organizations. Service activities are carried out in three stages, namely: planning, implementation and evaluation. The implementation carried out presentation of material on local wisdom values, participants created works and presented. The participants' response was positive towards the implementation of the service. Participants expressed their appreciation for the activities carried out.